The Effects of Shielding Blocks On Dose Parameters During Cobalt-60 Irradiation Of The Irregular Abdomen And Pelvis Fields (Annals of Medical Research, 2021)
None
Keywords: s : Irregular fields, totai abdomen, pelvis, dosimetri, cobalt-60, radiotherapy.